Pengaruh Social Media Platform , Financial Literacy, Dan Investment Motivation Terhadap Minat Berinvestasi Di Pasar Modal (Studi Kasus Pada Mahasiswa Generasi Z) - Muhammad Muslihul Hadi; Ronny Malavia Mardani; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2023)
AbstractThis study aims to determine the effect of Social Media platform, Financial literacy and Investment Motivation on students' interest in investing in the capital market. The type of research used is quantitative research, with data collection methods by distributing questionnaires. The sample in this study were 90 respondents and the data processing used the SPSS data processing program. This study has fulfilled the validity and reliability tests. The data analysis used in this study is the classical assumption test, multiple linear regression test, statistical test and the coefficient of determination. The variables used in this study are Social Media platform, Financial literacy and Investment Motivation, which are independent variables, while the dependent variable in this study is Interest in Investing in the Capital Market. Keywords: Social Media platform , Financial literacy, Investment Motivation.